From Inclusive Identities to Inclusive Societies: Exploring Complex Social Identity in the Macedonian Context - Pajaziti, Ali; Blazhevska Stoilkovska, Biljana; Frichand, Ana (Iliria College, 2016)
Republic of Macedonia is an entity described as cultural mosaic, with strong multiethnic and multi-confessional basis, it is a point where East and West meet, it is well-known for the system of Macedonian salad. But, this society even after 25 years of social transition and 2001 Ohrid Agreement did not achieve to find the way of conclusive peace, stability and social eudemonia. This diversity is issue that from time to time produces turbulences, especially at the line of two main identity groups Macedonians-Christian Orthodox and Albanians-Muslim community. Quantitative data in this study were obtained on a sample of 219 young adults from Skopje ( 95 of Macedonian and 17 of Albanian ethnicity) and Tetovo (76 of Albanian and 31 of Macedonian ethnicity), aged from 18 to 35 years (M=24.85, SD=3.2). Main research question is that if there exist differences between young Macedonians and Albanians in their ethnic, religious and national identity? The objective of this paper is to give a scientific picture how categories as gender, marriage, family, ethnicity, religion, living place, Balkan, Europe are percieved by the youth, all this in favour of using them in producing affirmative actions, more productive societal policies and constructive society-building. Multiple social identities: their complexity and inclusiveness, the correlation of identity variables with SII and SIC are among issues analyzed in this paper. National dominance was more frequent among Macedonians. Our findings demonstrate that Albanian participants expressed strong social identity, as Albanians and as being Muslims. Only social identity inclusiveness is significantly related to societal and political attitudes, but ethnicity should be taken into consideration whne this relationship is explored.
Keywords: Macedonia, identity, young people, perception(s), ethnicity, religion, complex identities